Long-Range Heterogeneous Electron Transfer of Ferrocene Functionalized Gold Nanoparticles Through Alkanethiol Bridges at Gold Electrodes - ZHANG, JIONG; WANG, LIHUA; WAN, YING; ZUO, XIAOLEI; SONG, SHIPING; ZHANG, ZHIZHOU; FAN, CHUNHAI (Asian Journal of Chemistry, 2010)
The heterogeneous electron-transfer rate constants between gold electrodes and ferrocene either attached to the electrode surface directly by an alkanethiol bridge or anchored to gold nanoparticles which adsorbed on the electrode were measured using cyclic voltammetry. For the ferrocene directly attached to the electrode through an undecanethiol linkage we found the different density of redox molecules exhibited different electron-transfer rate constants. In this work, the ferrocene anchoring to gold nanoparticles (AuNPs) led to very stable functionalized nanoparticles, which possessed well electrochemical activity.